Romantic Love Is Associated with Enhanced Inhibitory Control in an Emotional Stop-Signal Task - Song, Sensen; Zou, Zhiling; Song, Hongwen; Wang, Yongming; d’Oleire Uquillas, Federico; Wang, Huijun; Chen, Hong (Frontiers in Psychology, 2016)
Purpose: This study explored whether romantic lovers differ in emotion-related inhibitory control capacity from those who are single. Methods: 88 healthy undergraduate college students participated in the study. Half were currently in love and in a romantic relationship (love group, LG), and half were single and had never been in a romantic relationship (single group, SG). Based on duration of romantic relationship (i.e., love duration), the LG were further divided into two subgroups: “early stage love” and “longer periods of love”. All participants completed an emotional Stop Signal Task (eSST), which consisted of a variety of human face stimuli representing sadness (a negative emotion), as well as neutral emotions. Results: Results found that relative to SG, lovers showed greater inhibitory control [shorter stop-signal reaction time (SSRT)] during negative emotion condition trials. Furthermore, in early stages of love, SSRT for negative emotion condition trials was significantly shorter compared to that in “longer periods of love” or SG individuals, with no significant differences between the latter two groups. Conclusions: Compared with individuals who were single, early-stage lovers showed greater capacity for inhibiting action during presentation of negative emotional stimuli. Within a greater social context, greater inhibitory control capacity during early stages of love may be related to the successful formation of romantic relationships, particularly to the ability to persevere in goal-directed action despite negative emotional contexts such as that of sadness.